CROSS-CULTURAL COMMUNICATION: AN ANALYSIS OF TRADITIONAL FOOD IN CROSS-CULTURAL COMMUNICATION - Destiwati, Rita; Harahap, Junardi (PEOPLE: International Journal of Social Sciences, 2019)
Cross-cultural communication is a communication that binds the community to become an important part of the culture that brings the community into in it, because the cultural influences inherent from birth. The original culture that brings and becomes a strong part in society and fundamental in society. This study discusses cross-cultural communication in students at the University, which is taken in the private university and another state university at the Bandung. This research looks at food made in cross-cultural communication. The results of the study state that foreign people from Asia prefer typical foods such as fried rice and satay. However, students who are not Asian prefer food that is ate from anywhere they can eat. The Asia student wants to try the variants of food from the difference countries. than Asian prefer the food they eat, this is meaning that food that is more like food from their country is like students and then prefer to cook it themselves. So, that students from Asia prefer food from West Java, while students from outside food from their country so they prefer to cook by themselves. This is not general, just looking at the informants studied in this research article.